Rancangan Model Digitalisasi Pasar Tradisional Pasar Rare Angon Di Desa Gunaksa - I Kadek Arta Wiguna; Komang Agus Ariana (STMIK Royal, 2021)
Abstract: The increasing cases of covid-19 have an impact on the economy in Indonesia, especially on micro, small and medium enterprises (MSMEs). local communities who during this pandemic experienced a decline in income. Shoppers are starting to rarely come to the market and shop in person because of their fear of contracting Covid-19 and avoiding crowds that have been advised by the government. The digitalization of traditional people's markets is needed to improve the economy and reduce the spread of the covid-19 virus. The results of interviews with traders show the lack of sales at Rare Angon Market because few people know about the market. the method used by distributing questionnaires to find out in detail the existing problems. From these problems, a solution is needed to bridge between traders and buyers, this solution is in the form of digitizing the Rare Angon market by developing an application called